Factors affecting student’s purchase intension on innovative electric motorcycles in Bangkok and surrounding areas - Withayaruksun, Thanapol; Vuthisopon, Sujira; Saengnoree, Amnuay (Edelweiss Applied Science and Technology, 2025)
This research investigates the impact of three core factors—namely, product innovation characteristics, perceived value, and individual attitude—on the intention of university students in Bangkok and surrounding areas to purchase electric motorcycles. Additionally, the study aims to construct a structural equation model (SEM) illustrating the relationships among these variables. A quantitative approach was adopted, employing a structured questionnaire to collect data from 240 university students who had experience in motorcycle purchasing. A two-stage sampling method, including quota and purposive sampling, was applied. The data were analyzed using descriptive statistics, confirmatory factor analysis (CFA), and structural equation modeling (SEM). The findings revealed that product innovation characteristics, perceived value, and attitude each had a statistically significant and positive direct effect on purchase intention. Moreover, both product innovation and perceived value indirectly influenced purchase intention through the mediating role of attitude. Among these factors, product innovation characteristics exhibited the strongest total influence, followed by perceived value and attitude. An effective product innovation strategy that aligns with consumer values and nurtures positive attitudes is crucial in boosting students’ purchase intention. These insights provide actionable recommendations for manufacturers and marketers of electric motorcycles aiming to target young urban consumers. The research advances understanding in the field of consumer behavior toward sustainable transport, particularly electric motorcycles. By integrating innovation, value perception, and attitude within a cohesive model, the study offers a practical framework for addressing purchase behavior in a growing market segment.